2021
DOI: 10.3390/jcm10132928
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Quality of Life Changes after Hysteroscopic Treatment in Patients with Symptomatic Isthmocele—Preliminary Results

Abstract: Due to an increasing number of cesarean section deliveries, the common consequences of that surgery are observed more often in the population. One of them is the uterine cesarean scar defect known as niche or isthmocele. Most patients with that aliment are asymptomatic, but some of them can report abnormal uterine bleeding, pelvic pain, subfertility which can be the reason for reduced quality of life (QoL) of the patients. In our study, we analyzed the subjective feelings of changes in the severity of symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In addition, no complication occurred for any of our patients' .This proves that hysteroscopy is an ideal tool for management in patient with RMT > 2.5mm. Improvement in the abnormal uterine bleeding was in line with results of other previous studies [2,14,[18][19][20] .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, no complication occurred for any of our patients' .This proves that hysteroscopy is an ideal tool for management in patient with RMT > 2.5mm. Improvement in the abnormal uterine bleeding was in line with results of other previous studies [2,14,[18][19][20] .…”
Section: Discussionsupporting
confidence: 91%
“…None of the studies included a combination of women with and without infertility. An overview of the baseline characteristics, including niche features, is reported for the studies that included women diagnosed with infertility (Table 1) (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and women without infertility (Table 2) (36)(37)(38)(39)(40). Most studies evaluated HNR (N ¼ 14), and 7, 7, and 2 studies reported on VNR, LSNR, and LTNR, respectively.…”
Section: Study and Population Characteristicsmentioning
confidence: 99%
“…None of the studies that report about HNR, LTNR, or LSNR mentioned perioperative complications. However, 4 and 4 studies did not reported details about complications after HNR (25,29,33,38,39), and LSNR (30,33,38,39), respectively. In the 16 studies that reported on women with infertility, 8 reported a definition or duration of infertility.…”
Section: Study and Population Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations